Malmquist Productivity Index on Islamic Economics and Finance Research - Aam S. Rusydiana; Lina Marlina; Lina Nugraha Rani (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study proposes to review the implementation of Malmquist Productivity Index (MPI) in such research publications on the theme of Islamic economics and finance. It employs descriptive statistical analysis based on selected 102 article publications. The entire sample publications have published from 2006 to 2019. The results show that research using the MPI method has still been dominated by Islamic banks issues (73%) followed by Islamic insurance or takaful issue (12%), then zakat (8%), and Islamic microfinance issue (4%). The rest are issues about halal industry, waqf and Islamic REIT. Malaysia, Indonesia and Pakistan are the 3 countries with the most study areas compared to other countries. In addition, many MPI applications are implemented along with the use of DEA methods for measuring efficiency. The most approach used in 102 studies is the production and intermediation approach.Â Keywords: Malmquist Index, productivity, Islamic Economics, finance